The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1289/ehp.02110293
|View full text |Cite
|
Sign up to set email alerts
|

Effect of motor vehicle emissions on respiratory health in an urban area.

Abstract: Motor vehicles emit particulate matter < 2.5 microm in diameter (PM(2.5)), and as a result, PM(2.5) concentrations tend to be elevated near busy streets. Studies of the relationship between motor vehicle emissions and respiratory health are generally limited by difficulties in exposure assessment. We developed a refined exposure model and implemented it using a geographic information system to estimate the average daily census enumeration area (EA) exposure to PM(2.5). Southeast Toronto, the study area, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(60 citation statements)
references
References 51 publications
0
56
0
3
Order By: Relevance
“…Inhalation of chemicals may represent a direct route for chemicals to enter the blood stream and exert biological effects on target tissues. There are evidences that burning these fuels release harmful air pollutants that are associated with respiratory infections (Buckeridge et al, 2002), carcinogenic potencies (Mi et al, 2001) and amphibian malformations (Hopkins et al, 2000). The results of recombinant yeast bioassay of estrogenic compounds as presented in the current study indicated that weak estrogenic activities are also associated with emissions from fossil fuel combustion.…”
Section: Article In Pressmentioning
confidence: 55%
“…Inhalation of chemicals may represent a direct route for chemicals to enter the blood stream and exert biological effects on target tissues. There are evidences that burning these fuels release harmful air pollutants that are associated with respiratory infections (Buckeridge et al, 2002), carcinogenic potencies (Mi et al, 2001) and amphibian malformations (Hopkins et al, 2000). The results of recombinant yeast bioassay of estrogenic compounds as presented in the current study indicated that weak estrogenic activities are also associated with emissions from fossil fuel combustion.…”
Section: Article In Pressmentioning
confidence: 55%
“…Elevated levels of air pollution particles are associated with increased morbidity and mortality resulting from acute and chronic cardiopulmonary injury (1)(2)(3)(4). Inhalation of particulate air pollutants can trigger generation of reactive oxygen and nitrogen species in the airway epithelium, leading to expression of multiple proinflammatory cytokines and airway pathobiology (5).…”
mentioning
confidence: 99%
“…29,30 However, studies of other health outcomes, such as asthma hospitalizations and medication use and risk for various cancers, have provided less consistent evidence. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] Evidence also suggests that traffic density 49 and traffic proximity 50 may be linked to adverse preterm birth outcomes.…”
Section: Near-roadway Traffic and Healthmentioning
confidence: 99%